Understanding Insecticide Modes of Action and Resistance Management in Florida Horticulture - Hugh Smith; Adam Dale; Julien Beuzelin (EDIS)
This publication is designed to help UF IFAS Extension agents and members of the public understand insecticide modes of action and resistance management as they pertain to vegetables, field crops, turf, and ornamental plants.